Systematic review and meta-analysis comparing robotic total mesorectal excision versus transanal total mesorectal excision for rectal cancer - Chaouch, Mohamed Ali; Hussain, Mohammad Iqbal; Jellali, Maissa; Gouader, Amine; Mazzotta, Alessandro; da Costa, Adriano Carneiro; Krimi, Bassem; Khan, Jim; Oweira, Hani (Scandinavian journal of surgery, 2024)
Introduction: The best approach for total mesorectal excision (TME) remains controversial. Two recently described approaches are robotic TME (RTME) and transanal TME (TaTME). This systematic review and meta-analysis aimed to compare the outcomes between robotic surgery and TaTME in patients undergoing rectal cancer resection. - Methods: We structured this systematic review and meta-analysis according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines 2020 and Assessing the Methodological Quality of Systematic Reviews (AMSTAR) guidelines. An electronic search of relevant literature was conducted on 20 May 2023. The protocol was registered in PROSPERO (CRD42023435259). - Results: Eleven eligible nonrandomised studies were included in this study. The study included 2796 patients (RTME = 1800; TaTME = 996). The RTME group had a higher rate of complete TME. However, no significant differences were observed in mortality, morbidity, severe complications, operative time, conversion rate, anastomotic leak, hospital stay, CRM-positive resection margin, distal resection margin, number of harvested lymph nodes, abdominoperineal resection (APR) rate, or local recurrence between the RTME and TaTME groups. - Conclusion: The RTME technique may ensure a higher rate of complete TME than TaTME. However, no significant differences were observed in most postoperative outcomes and oncological safety between the RTME and TaTME groups. Evidence does not conclusively favor one technique over the other, highlighting the need for additional randomized controlled trials to better define their roles in rectal cancer surgery.
Erstmals online veröffentlicht: 19. September 2024
Gesehen am 14.01.2025